Contextualizing case reviews: A methodology for developing systemic safeguarding practices. Issue 1 (27th June 2017) - Firmin, Carlene
Abstract: This paper introduces a systemic methodology for reviewing professional responses to abuse between young people. The approach, "contextual case reviewing, " draws upon constructivist structuralism to assess the extent to which safeguarding practices engage with the social and public contexts of abuse. The paper conceptually compares the methodologies of contextual case review and other serious case review methods before drawing upon findings from 2 studies, which used the contextual case review methodology to explore the extrafamilial nature of peer‐on‐peer abuse and the ability of child protection practices to engage with this dynamic. Thematic findings from these studies regarding the practical interpretation of "significant harm" and "capacity to safeguard, " as well as their use within child protection assessments, are used to challenge conclusions of other case reviews, which imply that child protection procedures are sufficient for safeguarding young people. Contextual case reviews suggest that safeguarding practices, and the legislation that underpins them, are culturally, procedurally, and organisationally wedded to the context of the home, whereas insufficiently engaged with extrafamilial contexts of significant harm. The application of these issues require interrogation if social work systems are to provide sufficient mechanisms for safeguarding young people and families at risk of significant harm.